2013
DOI: 10.1186/1477-7819-11-309
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl Lewis X as a predictor of skip N2 metastasis in clinical stage IA non-small cell lung cancer

Abstract: Background: Radical segmentectomy has been performed for small-sized non-small cell lung cancer (NSCLC). However, underestimation of mediastinal lymph node metastasis in the absence of hilar or interlobar metastasis (skip N2) affects surgical strategy. Our aim was to investigate preoperative and intraoperative predictors of skip N2 in clinical stage (c-stage) IA NSCLC. Methods: From 1998 to 2011, 279 patients (155 men and 124 women) with c-stage IA NSCLC (230 pN0, 17 pN1, 12 skip N2, 20 non-skip N2) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Similar findings were shown by Kadota et al (1999) [ 34 ], suggesting CD15s correlates with distant metastatic lesions in lung carcinoma. Recently, elevated levels of CD15s were reported to be used as an independent marker to predict NSCLC patients at the metastatic stage [ 35 ], although, little is known about CD15s expression in CNS malignancies. We recently reported that CD15s overexpression was cell cycle dependent in high grade glioblastoma cells as well as in metastatic brain tumour cells originating from lung [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were shown by Kadota et al (1999) [ 34 ], suggesting CD15s correlates with distant metastatic lesions in lung carcinoma. Recently, elevated levels of CD15s were reported to be used as an independent marker to predict NSCLC patients at the metastatic stage [ 35 ], although, little is known about CD15s expression in CNS malignancies. We recently reported that CD15s overexpression was cell cycle dependent in high grade glioblastoma cells as well as in metastatic brain tumour cells originating from lung [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The modifications of cell glycosylation observed in cancers mainly affect the outer part of glycans, leading to the expression of cell surface antigenic sialylated structures that are strongly associated with a poor prognosis in certain tumors [1,2,3]. For example, sialyl-Lewis a (sLe a ) and sialyl-Lewis x (sLe x ) antigens are abnormally found on glycoproteins and glycolipids in several types of solid tumors and sLe x /selectin interactions are clearly involved in metastatic progression of gastric [4], lung [5] and prostate [6] cancers. These changes of cell glycosylation are mainly supported by the deregulation of the expression of glycosyltransferases (GTs) genes implicated in terminal glycosylation.…”
Section: Introductionmentioning
confidence: 99%
“…However, sometimes metastatic LNs can be detected far from the original tumor without being detected in the peritumoral area, which has been called skip metastasis. This unusual pattern of LN metastasis has been reported in various cancers, such as breast, colon, and lung cancer [3][4][5]. Several studies have also reported on skip metastasis in gastric cancer [7][8][9], in which the following factors could play a role: (1) occult metastasis or micrometastasis which was missed during routine examination of the perigastric (PG) area [10]; (2) direct lymphatic flow from the tumor to LNs in the extraperigastric (EP) area, bypassing the PG area [11-13; and (3) free cancer cells passing through PG LNs because of an unfit microenvironment for settling [14].…”
Section: Introductionmentioning
confidence: 99%